Chasing paper tigers: Need for caution and priorities in EU countervailing duties (CVDs) - Hosuk Lee-Makiyama (European Centre for International Political Economy (ECIPE), 2011)
A new trade war is looming as the EU is now embarking on its first countervailing duty (CVD) against Chinese subsidies over coated fine paper. As the EU gives a significant amount of subsidies to local production, China is not short of sectors to retaliate against - especially as the evidence in the paper case is weak: The share of Chinese exports is yet too small to inflict any injury on EU producers, and China holds less than 4% of the EU market; alleged subsidies through grants, subsidised electricity, VAT and tax rebates have little impact on the final price; and the main argument is based on an assumption that Chinese commercial banks are state owned and are thereby public bodies. Given the risk for retaliation, CVDs are a risky and costly means to buy time for sunset industries and as CVDs alone cannot remove subsidies in the target country, they are therefore often inferior to a WTO dispute. This calls for a new policy on CVDs where the EU only addresses urgent cases of serious injury against unsubsidised sectors with high value-added and where the EU represents a significant market share. China directs most of its subsidies to strategic emerging industries, and even amongst these sectors only a handful live up to these criteria.
Keywords: 330; Antidumping; EU-Politik; Grafisches Papier; China; EU-Staaten